ANALISIS KINERJA PEMASARAN PADA INDUSTRI OLAHAN GERABAH DI KABUPATEN TAKALAR PROVINSI SULAWESI SELATAN - Merry Margareth Pelupessy (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
The aims of the research were to anayze marketing performance of processing industry of earthenware vessels and to find out whether product,business,and theeffectiveness of distribution channel strategies have influence on the increase ofmarketing performance.The populations were the owners of processing businessof earthenware vessels in Pattalassang district of takalar Regency consisting120industries.The sample consisted of 57 industries selected using simple randomsampling method based on Rao formulae.The data were obtained in two step,i.e.library study and questionnaire.The measurement of variables used LIKERTScale which indicated the level of respondents agreement with a score raging from1 to 5 (really agre,agree,quite agree,not agree,really not agree).The datewereanalyzed using multiple linear regression analysis.The results of inferentialanalysis indicate that the variables of product(X1),business(X2),and theeffectiveness of distribution channel(X3) strategies have positive and significantinfluence on marketing performance either simultaneously or partially.Theobtained regression equation is y =1.115 + 0.525x1 +0.237x2 + 0.025x3.